THE EFFECT OF DEMOGRAPHIC CHARACTERISTICS ON RISK PERCEPTION AND INVESTMENT DECISION: AN EMPIRICAL STUDY IN VIETNAM - Su, Shu-Hui; Liu, Yao-Ling; Lee, Hsiu-Ling; Quy, Tran Thi Kim (Indian Journal of Finance and Banking, 2022)
The purpose of this study is to investigate how demographic characteristics, such as gender, age, income, investing experience, education, marital status, and occupation, affect risk perception and investment decision by surveying of investors in Vietnam. The research also examines the relationship between risk perception and investment decision. This paper helps researchers have a clear understanding of how Vietnamese investors with different demographic profiles will invest their money and how the demographic characteristics will affect their risk perception. The research discovers that demographic factors such as age, income, occupation, and investing experience have significant effects on the risk perception of investors meanwhile income, gender, and investing experience are strongly related to investment decision. The analysis result also verifies that risk perception is associated with investment decision. The survey data were collected from 167 samples including students, company employees, or people who run their own business with the age of 18 to 45. It was conducted for general investors and had practical implications for mutual funds, financial advisors, and bankers.JEL Classification Codes: G11, G40, G41.